Understanding and Implementation of Inheritance Distribution Among the Congregation of Abdillah Mosque, Jember: Pemahaman dan Implementasi Pembagian Waris di Kalangan Jamaah Masjid Abdillah Jember - Wira Yafi Baswara; Muhammad Galeh Satrianto; Moeh. Diki Purwanto; Muhammad Ridho Fauzan; Alva Rijalul Bayan (PT Syamilah Literasi Islami, 2025)
Inheritance law governs the distribution of a deceased individual's assets to their rightful heirs or family members. This research focuses on Masjid Abdillah Rabbani, situated in the Rabbani residential area, Kaliwates District, Jember Regency. Researchers have identified mosque attendees at Abdillah who have received inheritances within their families, leading to the interest in conducting this study. Employing a qualitative approach with a case study design, the objectives of this research are threefold: (1) To explore the concept of inheritance distribution as per the scholars of the madhabs, (2) To understand the congregation of Masjid Abdillah's perception of inheritance distribution, (3) To investigate the implementation of inheritance distribution among this congregation. The research findings suggest that, according to madhabs scholars, the science of inheritance concentrates on dividing the assets left behind by the deceased, not solely on the monetary value. This process initiates upon an individual's passing. In terms of the congregation's understanding at Masjid Abdillah: it was found that they are well-acquainted with the principles of Islamic inheritance laws. In the context of implementing inheritance distribution: (1) Some congregation members have adhered to Islamic inheritance principles, (2) While others face obstacles that hinder full compliance with these laws.